Advances of herbivore-secreted elicitors and effectors in plant-insect interactions - Wang, Huiying; Shi, Shaojie; Hua, Wei (Frontiers in Plant Science, 2023)
Diverse molecular processes regulate the interactions between insect herbivores and their host plants. When plants are exposed to insects, elicitors induce plant defenses, and complex physiological and biochemical processes are triggered, such as the activation of the jasmonic acid (JA) and salicylic acid (SA) pathways, Ca2+ flux, reactive oxygen species (ROS) burst, mitogen-activated protein kinase (MAPK) activation, and other responses. For better adaptation, insects secrete a large number of effectors to interfere with plant defenses on multiple levels. In plants, resistance (R) proteins have evolved to recognize effectors and trigger stronger defense responses. However, only a few effectors recognized by R proteins have been identified until now. Multi-omics approaches for high-throughput elicitor/effector identification and functional characterization have been developed. In this review, we mainly highlight the recent advances in the identification of the elicitors and effectors secreted by insects and their target proteins in plants and discuss their underlying molecular mechanisms, which will provide new inspiration for controlling these insect pests.